Crude Oil Price Fluctuation And Inflation In Nigeria - Apere, ThankGod Oyinpreye (Advances in Social Sciences Research Journal, 2017)
This research empirically investigated the relationship between inflation and oil price fluctuations in Nigeria with quarterly data over the period 1980:1 to 2015:4.Using secondary data obtained from the Central Bank of Nigeria (CBN) Statistical Bulletin 2015 and Energy Information Administration (EIA) short-term outlook, December, 2016. Vector autoregressive model econometric technique was adopted in analysing the data for this study with the following analysis carried out; the Lag length selection, VAR stability tests, VAR LM test for serial correlation, the Impulse Response Function and the Forecast Error Variance Decomposition. The study revealed that the response of inflation to oil price fluctuation is that as oil prices falls inflation fall also and a stable and positive oil price results in a stable negative inflation rate, thus the relationship between them( inflation and oil price fluctuation) is negative This study therefore recommends that the cost channels transmission should be weakened by further diversification of the Nigeria economy and enhancement of import substitution strategies. To facilitate the monetary authority in achieving lower inflation and stable economic growth targets counter-cyclical fiscal policies and effectively binding fiscal rules should be formulated and implemented.